High-Resolution Silt Distribution Mapping Using Ordinary Kriging From Borehole Data in a Geohazard-Prone Area - Taharin, Mohammad Radzif; Abdul Taha, Nazaruddin; Amaludin, Adriana; Abdul Razak, Mohd Shaifuddin; Zulkifli , Muhammad Farid; Ming, Chow Wai (Civil Engineering Journal, 2026)
Kundasang, Sabah, is one of the most geohazard-prone highland regions in Malaysia. Slope failures are frequently triggered by heavy rain. Silt-rich zones present a particular stability problem, since silt has low cohesion and drains faster than clay, which means that slopes can undergo rapid saturation and lose shear strength during sustained and intense rainfall. Previous research works in Kundasang have focused on landslide susceptibility through rainfall thresholds and GIS terrain analysis. However, depth-specific, high-resolution silt distribution maps have not yet been produced. This study addresses the research gap using geostatistical modeling of geotechnical data from boreholes to map silt distribution patterns. Soil samples from 70 boreholes were analyzed by classifying soil types down to 10 m depth in 2.5 m segments. Using Ordinary Kriging in ArcGIS 10.3, the best-fit semivariogram model for each depth was selected based on the lowest Root Mean Square Error values (ranging from 5.33 to 11.92). The findings reveal that high-silt zones (areas with over 30% silt content) cover around 40% of the study area and cluster mainly in western and northern Kundasang, particularly in the upper 7.5 m of soil. These correspond to areas previously documented as highly susceptible to rainfall-induced slope failures. The depth-specific silt distribution maps produced in this study provide important geotechnical inputs to enhance future landslide susceptibility assessments, improve slope stability analyses, and support risk-informed land-use planning for local authorities in geohazard-prone highland areas.